DAMPAK PENGGUNAAN METODE SILENT READING TERHADAP KEMAMPUAN PEMAHAMAN MEMBACA - Efa Silfia (Universitas Batanghari, 2024)
This research aimed to examine the impact of using the silent reading method on reading comprehension at SMAN 3 Sungai Penuh. This research used a pre-experimental design with a one-group pretest-posttest design type. The population of this research was all students of class XI Science at SMAN 3 Sungai Penuh which total of students were 155. The sample of this research was one of the XI Science classes, specifically class XI Science 3, using the cluster random sampling technique for sample selection. The data collection technique used was test. And the data analysis was conducted descriptively. The results of this research showed that before using the silent reading method, the average score was 48.31, with a maximum score of 68 and a minimum of 40. After using the silent reading method, the average score increased to 67.06, with a maximum score of 81 and a minimum of 61. The normality test showed that the pretest and posttest data had significant values more than α (0.375 > 0.05 and 0.715 > 0.05), indicating a normal data distribution. The impact of this research was important for teachers to choose appropriate teaching methods that align with the materials and learning objectives, and it can recommend the use of silent reading as an effective method to enhance the reading comprehension skills of eleventh-grade science students at SMAN 3 Sungai Penuh.